Bibliometric Analysis of Local Government Financial Reporting - Loso Judijanto; Yendri Deswin (Westscience Press, 2026)
This study aims to examine the development, intellectual structure, and emerging research trends in the field of local government financial reporting through a bibliometric analysis approach. The study utilizes scientific publications indexed in the Scopus database and applies bibliometric techniques using VOSviewer to analyze publication trends, citation performance, keyword co-occurrence, co-authorship networks, institutional collaboration, and country contributions. The findings indicate that research on local government financial reporting has experienced significant development, with major research focuses centered on financial reporting, public sector accounting, transparency, accountability, and government financial management. Citation analysis identifies influential studies that emphasize voluntary financial disclosure, governmental accounting reform, IPSAS adoption, and e-government as important foundations in strengthening public sector accountability. The keyword analysis reveals that recent research directions have expanded toward sustainability, risk management, earnings management, and digital transformation, demonstrating a shift from conventional reporting practices toward broader governance and accountability perspectives. Furthermore, collaboration analysis shows that research activities are dominated by countries such as the United States, the United Kingdom, Italy, Australia, and Indonesia, although international collaboration remains concentrated among specific research networks. This study contributes to the existing literature by providing a comprehensive mapping of knowledge development and identifying future research opportunities in local government financial reporting, particularly regarding technological innovation, sustainability-oriented reporting, and institutional reform in public sector financial governance.